Lockdown - Black, Peter Jay (Urban Outlaws, 2016)
"When an ally betrays the Urban Outlaws and steals a dangerous computer virus, the kids have no choice but to team up with a shadowy figure known as "The Shepherd" to take down their foe, and as they explore the unfamiliar streets and secret passageways of New York City and Los Angeles, they once again risk everything to save themselves. . . and the world"--